Al-Mufaddaliyyat wa Qimatuha al-Adabiyyah fi al-Hifaz 'ala al-Syi'r al-'Arabiy al-Qadim - Mohd Shahrizal, Nasir (2015)
1-The Arabic Ignorance poetry gathering in Mufaddaaliyyat was done by –AL Mufadhal Al Dhabi- to keep the ancient Arabic poetry .His choice of the Mufaddaaliyyat poets was not restricted on certain place of Arabia but it consisted the vast places of East and west of the Arabia , and this shows of it`s completence . and it`s considers the oldes book which collects samples of the Arabic poetry in the second Hijra century . 2-Mufaddaaliyyat is considering a validated poetry collection . and it represents the ignorance life with all it`s details even the geographical envornment . 3- the number of the ignorance poets is 53 in Mufaddaaliyyat, and the reason it seems for the high rank of the poetry in the ignorance era that had the superiority of the great and composed Arabic methods, that it is away from linguistic faults, so the Basryyoon and Kufa’s grammarian invoked with these ignorance poetry in the differential and grammatical issues.